INTEGRASI PENDIDIKAN KARAKTER DENGAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM MENANGKAL RADIKALISME DI SD/MI - Hafiz, Tanzil (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2024)
NKRI is again a country where the establishment is the result of funds with citizens of the Republic of Indonesia whose religious background is different from each other. The purpose of this writing is to know the emergence of the beautiful and also the solution in the time of the emergence of people in the midst of their people. The focus of this research is the material of Islamic Religious Education, Pancasila Education and Citizenship that is internalized since the age of PAUD / TK, SD / MI, SMP / MTs, SMA / MA / Higher Education. A writer's author is a kind of research literature. Data or materials for which research is a good name book, articles in journals, articles on blogspot, articles in magazines, newsletters, reported in magazines, all data sing6 with the title of this study. Analyze the data by reducing, miserable, and summarizing for solutions in the midst of the emergence of making beautiful beautiful. The results of his research directed that various parties both Akedemisi, The state with its laws and educational practitioners has emerged although it has sometimes still emerged, then with the integration of materials Of Islamic Religious Education and Pancasila Education and Citizenship education level PAUD / TK / BA up to higher education can be another solution in countering radicals by means of a material Islamic Religious Education and Education Pancasila and Citizenship (Four Pillars of Nationality and the symbol of the state so the main material in Education and Citizenship) and internalize that the Four Pillars of Nationality part of the Islamic regulations results ijtihad scholars who have agreed, therefore Muslims do not dare to decorate.